2021 AAHA/AAFP Feline Life Stage Guidelines. Issue 3 (March 2021) - Quimby, Jessica; Gowland, Shannon; Carney, Hazel C; DePorter, Theresa; Plummer, Paula; Westropp, Jodi
The guidelines, authored by a Task Force of experts in feline clinical medicine, are an update and extension of the AAFP–AAHA Feline Life Stage Guidelines published in 2010. The guidelines are published simultaneously in the Journal of Feline Medicine and Surgery (volume 23, issue 3, pages 211–233, DOI: 10.1177/1098612X21993657) and the Journal of the American Animal Hospital Association (volume 57, issue 2, pages 51–72, DOI: 10.5326/JAAHA-MS-7189). A noteworthy change from the earlier guidelines is the division of the cat's lifespan into a five-stage grouping with four distinct age-related stages (kitten, young adult, mature adult, and senior) as well as an end-of-life stage, instead of the previous six. This simplified grouping is consistent with how pet owners generally perceive their cat's maturation and aging process, and provides a readily understood basis for an evolving, individualized, lifelong feline healthcare strategy. The guidelines include a comprehensive table on the components of a feline wellness visit that provides a framework for systematically implementing an individualized life stage approach to feline healthcare. Included are recommendations for managing the most critical health-related factors in relation to a cat's life stage. These recommendations are further explained in the following categories: behavior and environmental needs; elimination; life stage nutrition and weight management; oral health; parasite control; vaccination; zoonoses and human safety; and recommended diagnostics based on life stage. A discussion on overcoming barriers to veterinary visits by cat owners offers practical advice on one of the most challenging aspects of delivering regular feline healthcare.